Clinicopathologic analysis of lymph node status in superficial esophageal squamous carcinoma. Issue 1 (December 2016) - Zhou, Yue; Du, Junjie; Li, Hai; Luo, Jinhua; Chen, Liang; Wang, Wei
Abstract Background Endoscopic approaches are gradually considered as a reliable treatment of intramucosal esophageal squamous carcinoma. However, endoscopic resection (ER) is limited by the potential lymph node metastasis (LNM) at various depths of mucosal and submucosal invasion. Methods We conducted a retrospective review of 498 patients with pT1 superficial esophageal squamous carcinoma (SESC) who underwent surgical resection from January 2008 to August 2015. Pathological characteristics of tumors including location, size, appearance, differentiation, invasion depth, and nodal status were reviewed, and risk factors were analyzed. Results LNM was found in 0.0, 2.7, 6.3, 18.2, 15.9, and 34.3 % of the m1, m2, m3, sm1, sm2, and sm3 lesions, respectively. Univariate logistic regression identified the presence of the tumor size > 2 cm (p < 0.05), the presence of the poor tumor differentiation (p < 0.05), and the depth of tumor invasion (p < 0.05) and angiolymphatic invasion (p < 0.05) to be the important risk factors associated with the prevalence of tumor-positive lymph nodes. These findings were confirmed in multivariate logistic regression as independent predictors for LNM. Conclusions ER is considered as a reliable treatment of m1 to m2 lesions. Radical surgical resection (SR) is the standard and irreplaceable therapy of sm1 to sm3 lesions. Patients with m3 lesions should undergo ER as the initial procedure for diagnosis. And this treatment is supported only by a successful description of the tumor's characteristics, including (1) only muscularis mucosa invasion and without invasion of the resection margins and (2) without any risk predictors for LNM. Otherwise, SR is recommended.